Bibliometric Analysis of Paper Publication for Artificial Intelligence on Librarianship System with Full and Fractional Method - Berliani, Kezia Putri; Yuadi, Imam (Edulib, 2022)
Knowing the bibliometric analysis of AI publications in the librarian system will be a great research opportunity because its development is very high. On the other hand, we can solve the convenience of current bibliometric analysis with bibliometric network applications, such as VOSViewer. However, the calculation is presented with two options, complete and fractional, for analysis. The bibliometric method is used to analyze the trend from time to time regarding AI in this library. The study uses Scopus to get data and VOSViewer to analyze, accompanied by trials with full and fractional methods. Through a restricted search of the past five years. AI has relevance to Librarianship Systems and trends in Digital Libraries. Then, it is found that there are differences in the calculation of the total and fractional methods that stand out in the bibliographic coupling approach. The development of AI in the librarian system is very high and is influenced by surrounding phenomena, while the choice of whole and fractional methods is not found to have absolute differences.